ANALISIS KESALAHAN PADA MATERI BARISAN DAN DERET DITINJAU DARI KEMAMPUAN PEMAHAMAN KONSEP DENGAN PEMBERIAN MATERI VIDEO PEMBELAJARAN - Wijayanto, Teguh Ari; Munandar, Dadang Rahman (IKIP Siliwangi, 2021)
This research was conducted because based on the results of observations, there were still many students who made mistakes in solving math problems from their ability to understand mathematical concepts and analyze the causative factors. This research is a descriptive study with a qualitative approach. The subject of this research was class XI MIPA 4 which was selected by purposive sampling for students with high, medium, and low level abilities and focused on the material of Sequences and Series. The instruments used in data collection were in the form of field notes during practice, tests, and documentation. The data were analyzed using a scale 4 analytic rubric according to Subanji and Mulyoto and an interactive model consisting of data reduction, data presentation and conclusion drawing. The results of the study showed that in solving the sequence and series questions the students made many misconceptions (KK) as many as 27 students. The factors that cause these errors are the learning process is less effective, less thorough in working on questions, readiness of students in participating in the learning process, facilities and infrastructure that support student learning in their respective homes, and students' understanding of the line and series material.